The effects of indigenous R&D activities on China's energy intensity: A regional perspective - Chen, Changhua; Huang, Junbing; Chang, Huigui; Lei, Hongyan (The Science of the total environment, 2019)
One of the most efficient and effective ways to cut energy intensity is through an increase in indigenous R&D activities. In the existing literature on the nexus of indigenous R&D and energy intensity, indigenous R&D activities are discussed as a whole, because they are assumed to be simple and homogeneous. Consequently, no detailed information on how indigenous R&D influences energy intensity can be obtained. In addition, regional imbalances are basically ignored. That may yield generalized results and policy implications for the whole of China but lack relevance for China's different regions. In this paper, the effects of indigenous R&D activities on energy intensity are analyzed by dividing R&D activities into three stages with three performers. The empirical results based on China's provincial data set covering the period 2000–2016 suggest that indigenous R&D is a major tool for cutting energy intensity; however, energy intensity is subject to statistically different effects from R&D activities in different stages and by different performers. The R&D activities in the experiment and development stage play a more important role in decreasing energy intensity, compared to the other two stages. In addition, R&D activities carried out by industrial enterprises contribute more to cutting energy intensity than those of independent R&D institutions and higher education. In a regional comparison, there is also clear evidence that the regional difference should not be omitted, suggesting that policy makers should pay more attention to coordinating the energy policies of different regions to maximize the policies' impacts. [Display omitted] •R&D activities are divided into three stages with three performers.•The energy intensity is subject to different effects from different kinds of R&D activities.•There are significant regional differences for the roles of R&D activities played in energy intensity.